Dampak Penggunaan Teknologi Internet terhadap Perkembangan Kognitif dan Perilaku Anak dalam Keluarga - Regiani, Ega; Dwiputri, Fira Ayu; Amaliyah, Sania; Herlambang, Yusuf Tri (Indo-MathEdu Intellectuals Journal, 2023)
The internet is an open global communications network that connects thousands of networks throughout the world. Internet use can now be accessed by all ages, from children, teenagers to adults. As a result, children use the internet more often at home than playing outside the home. The aim of this research is to determine the impact of excessive use of internet technology on the cognitive development and behavior of children in the family. The research method used is literature. Through this method, the author collects various national and international journal literature to study the concepts and theories contained therein. The research results show that excessive use of the internet, especially in multitasking media activities, can affect children's cognitive development in the form of poor focus performance in carrying out their tasks and easily distracted attention. Apart from that, the use of internet technology without supervision from parents has an impact on children's freedom of internet activities, which allows children to be exposed to content that is not appropriate for their age, such as cyber bullying, violent content and others. This can cause children to behave deviantly